Influence of Asana and Aerobic Exercises on Selected Physiological Variables of Pregnant Women and their Fetus - Jothi, K. (Recent Research in Science and Technology, 2010)
The purpose of the study was the influence of selected asana and mild aerobic exercises on selected physiological variables at prior to and immediately after exercises of pregnant women and their fetus from 28th to 36th weeks of gestational age. 30 pregnant women were taught asana and aerobic exercises for three weeks. A pilot study was conducted to ensure an optimum training programme. On the day of experiment pregnant women’s fetal heart rate, maternal heart rate, systolic and diastolic blood pressure, mean arterial blood pressure and oxygen saturation were obtained which was followed by asana and aerobic exercises. Immediately after the exercise the subjects’ response to the exercise on selected physiological variables were obtained. The experimental design used was 3 x 2 factorial design with repeated measures in one factor (Gestational age). TheÂ exercises caused a significant (p<0.05) increase in the Fetal heart rate, maternal heart rate to higher post exercise response when compared to the pre exercise response. However, this response did not differ for the three gestational age categories. There was no significant (p>0.05) interaction between the gestational age and the exercise response factors. Further the exercise programme did not cause any significant difference in the maternal systolic and diastolic blood pressure, mean arterial pressure and oxygen saturation in pre and post exercise response.